(untitled) (Communications in Computational Physics, 2010)
In this paper, we propose a simple model of opinion dynamics to construct social networks, based on the algorithm of link rewiring of local attachment (RLA) and global attachment (RGA). Generality, the system does reach a steady state where all individuals' opinion and the complex network structure are fixed. The RGA enhances the ability of consensus of opinion formation. Furthermore, by tuning a model parameter p, which governs the proportion of RLA and RGA, we find the formation of hierarchical structure in the social networks for p > pc. Here, pc is related to the complex network size N and the minimal coordination number 2K. The model also reproduces many features of large social networks, including the "weak links" property.